Good nutrition across the lifespan is foundational for healthy aging and sustainable development - Rodríguez-Mañas, Leocadio; Murray, Robert; Glencorse, Carole; Sulo, Suela (Frontiers in Nutrition, 2023)
Ensuring healthy lives and promoting wellbeing across the age spectrum are essential to sustainable development. Nutrition is at the heart of the World Health Organization (WHO) Sustainable Development Goals, particularly for Sustainable Development Goal 2/Subgoal 2, which is to End all forms of malnutrition by 2030. This subgoal addresses people of all ages, including targeted groups like young children and older adults. In recent decades, there have been marked advances in the tools and methods used to screen for risk of malnutrition and to conduct nutritional assessments. There have also been innovations in nutritional interventions and outcome measures related to malnutrition. What has been less common is research on how nutritional interventions can impact healthy aging. Our Perspective article thus takes a life-course approach to consider what is needed to address risk of malnutrition and why, and to examine how good nutrition across the lifespan can contribute to healthy aging. We discuss broad-ranging yet interdependent ways to improve nutritional status worldwide—development of nutritional programs and policies, incorporation of the best nutrition-care tools and methods into practice, provision of professional training for quality nutritional care, and monitoring health and economic benefits of such changes. Taken together, our Perspective aims to (i) identify current challenges to meeting these ideals of nutritional care, and to (ii) discover enabling strategies for improvement of nutrition care across the lifespan. In harmony with the WHO goal of sustainable development, we underscore roles of nutrition to foster healthy human development and healthy aging worldwide.